ANSWER
-3
Step-by-step explanation
The formula for the general term of a geometric sequence is:
![a_n=a_1\cdot r^(n-1)](https://img.qammunity.org/2023/formulas/mathematics/college/usnb6cvy5q0c41ojuruucgvjnfnf10g7si.png)
In this sequence the first term a1 = -2. With this and the second term a2 = 6 we can find the common ratio and then verify with the next terms:
![\begin{gathered} a_2=a_1\cdot r^(2-1) \\ a_2=a_1\cdot r \\ r=(a_2)/(a_1) \\ r=(6)/(-2) \\ r=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8a4lfncoiucy9rfrahcnwke29nmnrat4cf.png)
If we use this common ratio to find the 3rd and 4th terms we have to arrive to the same result as the given sequence:
![\begin{gathered} a_3=-2\cdot(-3)^2 \\ a_3=-2\cdot9 \\ a_3=-18\to OK \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/i1gkn6w5zg8y3ecc26829lnp7ba0pgyzk6.png)
![\begin{gathered} a_4=-2\cdot(-3)^3 \\ a_4=-2\cdot(-27) \\ a_4=54\to OK \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/31tekzvm0nt28xahcppzk9v8ly8n9644eu.png)
The common ratio of this sequence is -3